Tactile graphic: the possible form of information and inclusion of the visually impaired - Leia de Andrade; Fernando Luiz de Paula Santil (Universidade Estadual Paulista Júlio de Mesquita Filho, 2011)
Although the graphics are present in the textbooks, these are not so accessible to the blind. In this case you need to generate them in high relief to be allowed to read through the tactile sense. For research in the development of tactile graphics with students in 5th grade the urban perimeter of Maringá (PR), drew on the Piaget's theory, who directed the evaluation of the cognitive development of students in the tasks, and also semiology graphics proposed by Bertin, who helped design treatment information for this production. In order to show the importance of tactile graphics for visually impaired students, which are inserted into the regular classroom, it was evaluated the techniques of construction and production of tactile graphic, and the steps of reading material. The results show that the graphs constructed instigate exploration, as much as it was a favor to tactile perception. It is necessary to respect the "living space" of the chart, in the case indicated by the distance between the hands. Regarding reading, the difficulties encountered were the identification of form, the notion of scale and coordinate system.